Modflow model in the assessment of water conditions in forest areas. (14th March 2023) - Wróbel, Michał; Brandyk, Andrzej; Tereba, Anna
The effects of climate change are being felt on many levels. One of them are forests and the water conditions in their area. There has been a significant decline in the water table, leading to changes in forest ecosystems. Therefore, it is important to take measures to reduce the negative impact on water conditions. Tools such as mathematical models of groundwater flow can support this action. This manuscript presents the possibilities of applying the Modflow model in forest areas. The analysis confirms that the model can be successfully applied. It was shown that the model is suitable for accurate determination of changes in the amount of water in the soil. In the studied example, the increase in groundwater retention when 50 cm high dams were used was about 27% compared to the variant without dams. When 100 cm high dams were used, the increase in water retention was about 38%.